EMPATI DALAM PENGEMBANGAN PASAR IKAN APUNG DI AREA KAMAL MUARA - Jonathan Yang; Mieke Choandi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Traditional fishermen in Kamal Muara face various significant challenges in carrying out their fishing activities, which directly affect their life conditions. In this context, an empathetic architectural approach can play an important role in designing sustainable and inclusive solutions to improve their well-being. There are 2 main factors that hinder the growth of fishermen's welfare, the first is the economic factor where fluctuations in fish prices, high production costs, low access to business capital and credit, and market uncertainty are economic factors that hinder the success of the fishing profession. Both environmental factors where climate change, environmental damage such as degradation of marine habitats and decreased fish stocks, as well as restrictions on access to fishing areas are environmental factors that hinder the sustainability of the fishing profession. The empathic architectural design proposes the development of a floating fish market in Kamal Muara which is able to provide equal access and opportunities for traditional fishermen in managing and utilizing the floating fish market. In addition, the design must also pay attention to the needs of the environment and the surrounding nature, and create spaces that are connected, inclusive, and respect equality among market users. Keywords: empathic architecture; economic factors; environmental factors; fish markets; traditional fishing Abstrak Para nelayan tradisional di Kamal Muara menghadapi berbagai tantangan yang signifikan dalam menjalankan kegiatan perikanan mereka, yang secara langsung mempengaruhi kondisi kehidupan mereka. Dalam konteks ini, pendekatan arsitektur yang empatik dapat memainkan peran penting dalam merancang solusi yang berkelanjutan dan inklusif untuk meningkatkan kesejahteraan mereka. Terdapat 2 faktor utama yang menghambat pertumbuhan kesejahteraan para nelayan, pertama faktor ekonomi dimana fluktuasi harga ikan, biaya produksi yang tinggi, rendahnya akses terhadap modal usaha dan kredit, serta ketidakpastian pasar merupakan faktor-faktor ekonomi yang menghambat keberhasilan profesi nelayan. Kedua faktor lingkungan dimana perubahan iklim, kerusakan lingkungan seperti degradasi habitat laut dan penurunan stok ikan, serta pembatasan akses ke wilayah perikanan menjadi faktor-faktor lingkungan yang menghambat keberlanjutan profesi nelayan. Desain arsitektur empati mengusulkan pengembangan pasar ikan apung di Kamal Muara yang mampu memberikan akses dan kesempatan yang sama bagi para nelayan tradisional dalam mengelola dan memanfaatkan pasar ikan apung. Selain itu, desain tersebut juga harus memperhatikan kebutuhan lingkungan dan alam sekitar, serta menciptakan ruang yang keterhubungan, inklusif, dan menghargai kesetaraan antar pengguna pasar.